Propaganda in the Gubernatorial Candidate in East Kalimantan Published in Online News Portal - Geroda, Godefridus Bali; Arbain, Arbain; Nur, Dedi Rahman (Center of Language and Cultural Studies [CLCS], 2019)
Propaganda can be identified using basic kinds of propaganda and seven techniques to present propaganda. White, Black, Agitation, Integration, Disinformation, Bureaucratic, Counterpropaganda, Hate, and Deed is the most useful categorization of propaganda according to Cunningham which is includes in nine basic categories of propaganda. The focus of this study is to analyze context and techniques of propaganda used in Online News Portal of East Kalimantan. The analysis of the content and techniques of propaganda obtained from the news articles in Online News Portal is therefore to explore how a certain message is described. The result show that present message in the propaganda, propagandist in in Online News Portal used seven techniques: (1) name calling, (2) glittering generalities, (3) transfer, (4) testimonial, (5) plain folks, (6) bandwagon, and (7) card stacking.